2008
DOI: 10.2147/cia.s213
|View full text |Cite
|
Sign up to set email alerts
|

Study of the intima-media thickening in carotid arteries of healthy elderly with high blood pressure and elderly with high blood pressure and dyslipidemia

Abstract: ObjectiveThe objective of this study was to assess the mean intima-media thickening of carotid arteries of elderly subjects, and its relationship with age, anthropometric measurements, high systolic blood pressure and dyslipidemia.MethodsIn this investigation, 129 subjects were enrolled between 1995 and 1998, age ranging from 29 to 94 years. They were assigned to one of 4 groups, including 2 control groups (group I, of healthy younger subjects; group II of healthy elderly subjects). Groups III and IV included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
2
5
0
2
Order By: Relevance
“…Similar relationships were found in this study between CIMT and hypertension, current smoking, and higher levels of SBP, FBG, and LDL-C. However, in contrast with previous studies that found a significant correlation between SBP and mean CIMT 35 36 37 38 , a negative correlation was observed between CIMT and DBP and TG in the current study. The exact causes are unknown, and further prospective large population-based studies are needed.…”
Section: Discussionsupporting
confidence: 71%
“…Similar relationships were found in this study between CIMT and hypertension, current smoking, and higher levels of SBP, FBG, and LDL-C. However, in contrast with previous studies that found a significant correlation between SBP and mean CIMT 35 36 37 38 , a negative correlation was observed between CIMT and DBP and TG in the current study. The exact causes are unknown, and further prospective large population-based studies are needed.…”
Section: Discussionsupporting
confidence: 71%
“…This evidence, in combination with findings that dysregulation of these physiological processes are associated with each other and with atherosclerotic disease (Clinton & Libby 1992; de Freitas et al 2008; Flaa et al 2008; Ross 1986, 1999), suggests that stressed caregivers may potentially experience higher levels of arterial damage over time. Moreover, chronically stressed caregivers also exhibit increased cardiovascular arousal in response to acute psychological stress (Aschbacher et al 2008; Mausbach et al 2005), which has been associated with increased carotid intima-media thickness (IMT) (Alevizaki et al 2007; Steptoe et al 2006), a marker of subclinical atherosclerosis (Lorenz et al 2007).…”
Section: Introductionmentioning
confidence: 80%
“…Different ethnicities may have different implications of thickening in different parts of the carotid artery due to HTN [ 6 ]. The literature is ambiguous as to the relationship of HTN with the presence of carotid plaque, as some studies showed a significant association between HTN and plaque presence [ 7 ], while other studies found no association [ 8 ]. As carotid thickening occurs in the early stages of atherosclerosis and plaque forms at later stages, it is said that the carotid IMT is a marker of early-stage subclinical atherosclerosis, and plaque presence is a marker of late-stage subclinical atherosclerosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%